The configuration between supply chain integration and information technology competency: A resource orchestration perspective - Liu, Hefu; Wei, Shaobo; Ke, Weiling; Wei, Kwok Kee; Hua, Zhongsheng (Journal of Operations Management, 2016)
AbstractResearch indicates that deploying appropriate information technology (IT) competency in a manner that fits the supply chain integration (SCI) of a firm induces superior firm performance; however, our understanding of how to empirically conceptualize and assess the performance effect of the fit remains limited. Drawing upon resource orchestration theory and the literature on fit assessment methodologies, our study employs both a contingency and a configuration perspective to conceptualize and operationalize “fit.” The results of a survey of 196 firms in China provide the first empirical evidence for the existence and nature of interrelationships between multiple components of SCI and IT competency and their effects on firm performance. In particular, fit as “moderation” approach indicates that IT competency could strengthen the relationship between SCI and both operational and financial performance. Fit as “profile deviation” approach further reveals that the more similar the IT competency configurations are to those of the top performers in the high‐level SCI group, the higher their operational and financial performance are. However, in the medium‐ and low‐level SCI groups, the SCI‐IT competency fit is significantly positively associated with financial performance and insignificantly associated with operational performance. The theoretical contributions and managerial implications of the study are discussed.